Anxiety Sensitivity and Quality of Life in Patients with Acne - Acer, Ersoy; Altınoz, Ali Ercan; Erdogan, Hilal Kaya; Agaoglu, Esra; Yuksel Canakcı, Nihan; Saracoglu, Zeynep Nurhan (Annals of dermatology, 2019)
Anxiety sensitivity (AS) is a continuous fundamental fear and defined as extreme fear of anxiety sensations and symptoms. High AS can cause tendency to anxiety disorders. There are many studies evaluating the anxiety in patients with acne; however, AS has not been investigated. We aimed to investigate AS in patients with acne. Two hundred and fourteen acne patients and 117 healthy control subjects, aged older than 16 years were enrolled in the study. Severity of acne was evaluated by Global Acne Grading System. The acne patients and healthy controls were asked to complete the anxiety sensitivity index-3 (ASI-3), the Beck anxiety inventory (BAI) and the Turkish version of acne quality of life index. Anxiety and AS levels in acne patients were significantly higher than healthy controls ( <0.001). Quality of life was impaired in acne patients. Quality of life was negatively correlated with anxiety and AS levels in acne patients ( =0.014, =0.019, respectively). There was no correlation between quality of life and disease severity ( =0.556) and also there was no correlation between psychiatric scale scores (ASI-3, BAI) and disease severity ( =0.147, =0.871, respectively). To our knowledge, our study is the first to report that AS is high in acne patients. Clinically, our results suggest that there might be a relationship between AS and acne. We conclude that further studies are needed in order to clarify the relationship between acne and AS and to investigate the efficacy of cognitive behavioral treatments in acne patients.